Prior learning assessment: Systematic review of academic literature - Catherine A. Cherrstrom,; Carrie J. Boden; Todd Sherron; Lindsey Wilson (Adult Education Research Conference, 2021)
Many argue a college degree is more important than ever and required for many occupations. However, pursuing one requires time and money. Prior learning assessment (PLA) offers one solution to overcome such barriers by documenting outside learning through competency portfolios or assessment testing to receive academic credit. The purpose of this systematic literature review was to examine the academic literature related to PLA within the United States. The review searched 669 databases, across 72 disciplines/fields, and yielded 47 peer-reviewed journal articles, published in 14 journals, during the last decade. Findings included six major themes with implications for adult education theory and practice.
Keywords: prior learning assessment; PLA; systematic literature review; adult learners; non-traditional students